An empire on trial race, murder, and justice under British rule, 1870 - 1935 - Wiener, Martin J. 1941- (Cambridge Univ. Press, 2009)
'An Empire on Trial' explores the issue of interracial homicide in the British Empire during its height - examining these incidents and the prosecution of such cases in each of seven colonies scattered throughout the world.